A proposed module on the concept heritage and national identity in the new social studies for grade six - Coruña, Lina Molina (1977)
The purpose of the study was to propose a module on the concept heritage and national identity for grade six. The module that was proposed in the study has for its sub-concepts, material heritage, non-material heritage, and national consciousness. It consists of the unit and four lessons. Each lesson is accompanied by several varied learning activities. The basic components of the unit are the overview, objectives, pretest, learning activities and post test. The new Scope and Sequence of the New Social Studies prepared by the Department of Education and Culture, Elementary Division was used in the selection of the major concepts, sub-concepts, generalization and elated ideas. In summary, the modular approach appears to be an effective and economical way of developing specific knowledge and skills. Because it is largely self-contained, it induces learning with minimum teacher direction and supervision. Individualized instruction indicates advantages for both the teacher and the child that is not found in other teaching approaches.